The mediating role of sleep quality on the relationship between physical activity and social anxiety disorder among Chinese college freshmen - Yingying Liu; Zizheng Nie; Haokai Dong; Linpei Shou; Jiaoyang Xu; Qinglong Cao; Yitian Shi; Chenyang Wu; Mu Zhang; Jun Yang; Shufen Han (Frontiers in Psychology)
ObjectivesSocial anxiety disorder (SAD) profoundly impacts the wellbeing of college students, both physically and psychologically. This study aimed to examine the mediating role of sleep quality on the relationship between physical activity and SAD among Chinese college freshmen.MethodsThis was a cross-sectional study enrolling 1,408 participants through convenience sampling. Participants self-reported their physical activity, sleep quality, and social anxiety status using an electronic questionnaire.ResultsThe overall prevalence of SAD was 33.05%. A significant negative association was observed between physical activity and SAD (adjusted β = −0.054, 95% CI: −0.053 to −0.001). Mediation analysis indicated that sleep quality may mediated 24.33% of the association between physical activity and SAD (indirect effect estimate = −0.009, direct effect estimate = −0.028, p < 0.01).ConclusionsLess physical activity is associated with SAD among Chinese college freshmen, and this relationship is partially mediated by poor sleep quality. It is recommended that educational institutions implement programs to promote regular physical exercise and enhance sleep quality to mitigate the impacts of SAD in this population.